Seasonality effects on chemical composition, antibacterial activity and essential oil yield of three species of Nectandra - de Oliveira Ferraz, Elza [UNESP]; Vieira, Maria Aparecida Ribeiro; Ferreira, Maria Izabela [UNESP]; Fernandes, Ary [UNESP]; Marques, Márcia Ortiz Mayo; Minatel, Igor Otavio [UNESP]; Albano, Mariana [UNESP]; Sambo, Paolo; Lima, Giuseppina Pace Pereira [UNESP] (Public Library of Science (PLoS), 2018)
In this study, we aimed to determine whether seasonality affects the content, chemical composition, and antimicrobial activity of essential oils (EOs) from the leaves of three species of Nectandra (Nectandra megapotamica, Nectandra grandiflora, and Nectandra lanceolata) native to the Atlantic rainforest, Sao Paulo state, Brazil. In addition, we identified the compounds potentially related to the antimicrobial activity. Leaves were randomly collected in the middle of winter (August), spring (November), summer (February), and autumn (May). The influence of seasonality on the content and chemical composition of EOs from the Nectandra species was evident in this study. The EOs from N. lanceolata and N. grandiflora were characterized by similarities in the chemical composition and had a higher relative proportion of oxygenated sesquiterpenes. N. megapotamica presented a different chemical profile, with plenty of monoterpenic and sesquiterpenic hydrocarbons. Changes in the EO chemical profile because of seasonality were shown by the similarities between the EOs obtained in spring and autumn and the differences between the EOs obtained in summer and winter. The EO from the leaves of N. megapotamica harvested in winter and spring showed the highest control of the growth of Escherichia coli, and this antimicrobial action can be related to the monoterpenes α-pinene and β-pinene as well as myrcene and limonene. The minimum inhibitory concentration (MIC) of the EO from the leaves of N. lanceolata harvested in summer and autumn was lower against the gram-positive bacterium Staphylococcus aureus and can be related to the sesquiterpene hydrocarbons isobicyclogermacrenal, epi-zizanone, and germacrene B.